The Effect Of Person Organization Fit And Job Satisfaction On Organizational Citizenship Behavior (OCB) In Uptd Bengkulu Job Training Employees - Jumadi, Muhammad; Ekowati, Sri (Journal of Management, Economic, and Accounting, 2025)
This study aims to determine the influence of person organization fit and job satisfaction on organizational citizenship behavior (OCB) in employees of UPTD Job Training Bengkulu, both partially and simultaneously. The object of this study is 49 employees of the Bengkulu Labor UPTD. In this study, the author used a data collection method by observation and distributing questionnaires. The data analysis techniques used in this study used instrument tests, respondent response analysis, classical assumption tests, multiple linear regression analysis, determination coefficients (R2) and hypothesis tests. The results of this study show that person organization fit has a positive and significant effect on organizational citizenship behavior (OCB) in employees of UPTD Job Training Bengkulu. Then the job satisfaction variable showed a positive and significant influence on organizational citizenship behavior (OCB) in employees of UPTD Job Training Bengkulu. So, from the results of the research that has been carried out, it can be concluded that person organization fit and job satisfaction have a partial and simultaneous effect on organizational citizenship behavior (OCB) in employees of UPTD Job Training Bengkulu.